Configuring a blueprint for Malaysian SMEs to survive through the COVID-19 crisis: The reinforcement of Quadruple Helix Innovation Model - Islam, Ariful; Jerin, Ishraq; Hafiz, Nusrat; Tali Nimfa, Danjuma; Abdul Wahab, Sazali (Journal of Entrepreneurship, Business and Economics, 2021)
When something unpredictable creates turbulence, the result can be disastrous not only for Malaysian SMEs but also for the country’s economic outline as well. So, how can SMEs survive the current crisis period caused by the COVID-19 pandemic? Actually, there are no straight answers. At this point, the study aims to serve a wider understanding of how an adjustable configuration of different strategic initiatives can help Malaysian SMEs endure through the crisis based on the QHIM mechanism. The study has embraced a qualitative approach on the basis of online focus group discussion with the support of an expert facilitator. The data collection process includes 10 participants from various fields, such as academia; banking, NGOs and SMEs. The study also collected secondary information through different newspapers, magazines, websites, E-libraries, documentaries, and related journal sources. Because SMEs are operating in uncertain conditions, the findings from the discussions suggest that an adjustable integration of various ranges of initiatives, such as access and management of financial resources, exploration-exploitation of opportunities, efficient negotiation, digital adoption, and leadership commitment can help SMEs to endure throughout this crisis. The findings also contend the intervention of innovation and calculated risk-taking within the configuration. The proposed conceptual model serves as an important mechanism for policy-makers and owner-manager of SMEs to understand how adjustments in identified initiatives can play a vital role regarding survival in this crisis. It provides recommendations for SMEs and on how to remain competitive through resilience and renewal strategies. The study contributes to the existing literature in crisis management and identifies the survival and resilience strategies of SMEs in developing regions during a long-lasting crisis. It also serves as a unique approach to how the Quadruple Helix perspective can be a vital concept in the survival process. Research paper Keywords: COVID-19; Crisis management; Digitalization; Innovation; SMEs Reference to this paper should be made as follows: Islam, A., Jerin, I., Hafiz, N., Tali Nimfa, D., & Abdul Wahab S. (2021). Configuring a blueprint for Malaysian SMEs to survive through the COVID-19 crisis: The reinforcement of Quadruple Helix Innovation Model. Journal of Entrepreneurship, Business and Economics , 9 (1), 32–81.